Indutores de resistência à antracnose e à mancha angular no feijoeiro comum - Gontijo Neto, Geraldo Ferreira (2015)
The development of new alternatives for disease control is of paramount importance to ensure the agricultural crops‟ productivity and sustainability of production systems. In this study the objective was to evaluate different resistance inducers to the control of anthracnose and angular leaf spot and their influence on productive performance of the common bean crop. A trial was conducted in a greenhouse, evaluating two calcium silicate doses (0 and 220 mg.dm -3 ) combined with seven foliar treatments [potassium silicate, acibenzolarS-methyl (ASM), orthophosphate, manganese phosphite, manganese sulfate, fungicide and water] on the severity and incidence of anthracnose and the growth of common bean plants. In the field, two assays (Lambari and Luminárias-MG) it was assessed six foliar treatment effect (five inducers of resistance and water), combined with two fungicides levels (with and without) on the control of anthracnose and angular leaf spot on the yield of bean grains. The statistical design was completely randomized in a greenhouse, while in the field was a randomized blocks, both with four repetitions. It was concluded that under controlled conditions, inducing molecules of resistance influenced the incidence and severity of anthracnose in common bean plants. Calcium silicate applied to equivalent dose provided by the corrective silicate in the field does not influence the bean growth neither the anthracnose development under controlled conditions. Inducers‟ use when combined with fungicides, provides no additional effect on disease control neither in common bean productivity when combined with fungicide, remaining chemical control with fungicides the best alternative for disease control under field conditions.